2000
DOI: 10.1111/1468-5957.00304
|View full text |Cite
|
Sign up to set email alerts
|

Free Cash Flow, Golden Parachutes, and the Discipline of Takeover Activity

Abstract: We conjecture that golden parachutes are initiated when the agency cost of free cash flow is most severe. We examine the relation between golden parachutes and investment levels in firms that have been successfully acquired. Our results support these three conclusions. First, target firms overinvest prior to an acquisition when golden parachutes are present. Second, the acquirers of targets with golden parachutes reduce investment subsequent to the takeover. Third, the reversal in capital investment by the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
2
7
1
Order By: Relevance
“…predictions of the managerial entrenchment theory regarding excess returns to targets, bidders, and bidder/target pairs are all supported by the data. This paper provides additional evidence consistent with Subramaniam and Daley (2000) who found that takeover targets with GPs over-invest in physical capital in the years preceding a takeover and that after the takeover the investment activity of the combined entity reverses that over-investment. Evidence in these papers are consistent with GPs reflecting severe cases of managerial entrenchment.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…predictions of the managerial entrenchment theory regarding excess returns to targets, bidders, and bidder/target pairs are all supported by the data. This paper provides additional evidence consistent with Subramaniam and Daley (2000) who found that takeover targets with GPs over-invest in physical capital in the years preceding a takeover and that after the takeover the investment activity of the combined entity reverses that over-investment. Evidence in these papers are consistent with GPs reflecting severe cases of managerial entrenchment.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with managers using their power to entrench themselves. Subramaniam and Daley (2000) provide evidence that takeover targets with GPs overinvest in physical capital in the years preceding a takeover and that after the takeover the investment activity of the combined entity reverses that over-investment. This is consistent with GPs reflecting severe cases of managerial entrenchment.…”
Section: (I) Golden Parachutes As Entrenchment Devicesmentioning
confidence: 88%
See 1 more Smart Citation
“…The golden parachute frequency in our paper is substantially higher than that found in other 13 studies (Cotter and Zenner, 1994;Subramaniam and Daley, 2000;and Lefanowicz, Robinson, and Smith, 2000).…”
Section: Descriptive Statisticscontrasting
confidence: 82%
“…Golden parachutes generally guarantee the contract holder a continuation of base pay and bonus for one to five years, the immediate vesting of any stock options, insurance coverage, availability of outplacement assistance, and acceleration of pension plan qualifications (Patterson, 2002). These clauses do not require shareholder approval to be adopted, but necessitate only an agreement between the manager and the board of directors (Subramaniam and Daley, 2000). Among the most cited reasons for the adoption of golden parachutes are: the attraction and retention of key executives, keeping the management team intact, and deterring a hostile takeover by making the transaction more expensive for bidders (Henderson, 1997).…”
Section: Description Of Special Attributes Of Ceo Compensation Contractsmentioning
confidence: 99%